Poppers maculopathy as an effect of drug poisoning. A clinical case - A. V. Zinov’eva; E. E. Ioyleva; N. A. Gavrilova (Российский офтальмологический журнал)
In recent years, the range of combined narcotic drugs has widened. New chemical modifications  have emerged, including so-called designer drugs, whose action on the body and in particular on the state of vision is increasingly difficult to determine. While the problem of drug abuse is growing drastically, timely detection of a possible toxic damage to the eye induced by drugs and reliable diagnosis differentiating such damage from other etiologies becomes a topical practical issue. The paper presents a clinical case of poppers maculopathy  (poppers being a slang name of aromatic volatile alkyl nitrite compounds). Ophthalmological  manifestations and differential diagnostic criteria of the damage are described. The mechanisms of action and possible treatment methods are discussed.